Cationic poly-l-lysine-encapsulated melanin nanoparticles as efficient photoacoustic agents targeting to glycosaminoglycans for the early diagnosis of articular cartilage degeneration in osteoarthritis. Issue 28 (4th July 2018) - Chen, Liang; Ji, Yu; Hu, Xiaoming; Cui, Cao; Liu, Hong; Tang, Yufu; Qi, Baiwen; Niu, Yahui; Hu, Xiang; Yu, Aixi; Fan, Quli
Abstract : Cartilage degeneration is the hallmark of osteoarthritis (OA) and its early diagnosis is essential for effective cartilage repair. Abstract : Cartilage degeneration is the hallmark of osteoarthritis (OA) and its early diagnosis is essential for effective cartilage repair. However, until now, there was still a lack of imaging modalities that can accurately detect and evaluate cartilage degeneration in its early stage. Herein, we introduce endogenous melanin nanoparticles (MNPs) encapsulated by poly-l -lysine (PLL) as positively charged contrast agents for the accurate photoacoustic (PA) imaging of cartilage degeneration through its strong electrostatic interaction with anionic glycosaminoglycans (GAGs) in the cartilage. PLL–MNPs presented high PA intensity, photostability and biocompatibility. In vitro PAI studies showed that PLL–MNPs with a zeta potential of +32.5 ± 9.3 mV had more cartilage uptake and longer retention time than anionic MNPs, and generated a positive relationship with the GAG content in the cartilage. After administration via intra-articular injection in living mouse models, PLL–MNPs exhibited about a two-fold stronger PA signal in a normal joint (with high GAG content) than an OA joint (with low GAG content). Furthermore, the obtained PAI results provided accurate information of the GAG content distribution in the OA knee joint. Consequently, by detecting and analyzing the changes of the GAG content in OA cartilage using PAI, we can clearly distinguish early OA from late OA and monitor the therapeutic efficacy in OA after drug treatment. All PAI results were examined histologically.